Analyzing the Impact of an 8-Week Structured Physical Activity Program on Health-Related Fitness in Bhutanese Seventh-Grade Students - Lhendup, Gayley; Savagpun, Pufa; Tiaotrakul, Arphat (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to evaluate the impact of an 8-week physical activity program (PAP) on health-related fitness (HRF) components of seventh graders in Bhutan. Its emphasis areas included assessing the program’s effects on cardiorespiratory endurance, muscular strength, muscular endurance, flexibility, and body composition. Materials and methods. Sixty-two students were allocated into two groups using simple random sampling: a control group (n = 31) following the standard physical education curriculum and an experimental group (n = 31) participating in the PAP utilizing the FITT (frequency, intensity, time, and type) principle. Fitness Gram assessments were used to measure HRF before implementing the intervention. Independent t-tests were used to compare results between groups, whereas paired t-tests were used to compare pre-test and post-test scores within groups. Results. All HRF components demonstrated notable improvements in the experimental group. Cardiorespiratory endurance increased from a mean of 23.23 to 30.57 (p < 0 .05), muscular strength — from 7.47 to 12.37 (p < 0.05), muscular endurance — from a mean of 10.10 to 16.40 (p < 0.05), and flexibility — from 27.98 to 29.85 (p < 0.05). It was additionally observed an improvement in body composition, with a notable decline in BMI. Conversely, the control group showed a less significant decrease in flexibility and BMI, while demonstrating marked enhancements in cardiorespiratory endurance, muscular strength, and muscular endurance. Conclusions. The study indicates that the organized PAP was more effective than the standard physical education curriculum in improving HRF components. These findings suggest that the implementation of structured PA programs using the FITT principles can lead to enhanced physical fitness and health-related outcomes among children and young people.